2021
DOI: 10.3390/ijerph182312632
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Untreated Disorder and Cannabis Use: An Observational Study on a Cohort of Young Italian Patients Experiencing Psychotic Experiences and Dissociative Symptoms

Abstract: Background: The Duration of Untreated Psychosis (DUP) is the time between the first-episode psychosis (FEP) and the initiation of antipsychotic treatment. It is an important predictor of several disease-related outcomes in psychotic disorders. The aim of this manuscript is investigating the influence of cannabis on the DUP and its clinical correlates. Methods: During years 2014–2019, sixty-two FEP patients with and without cannabis use disorder (CUD) were recruited from several Italian psychiatric hospitals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
(82 reference statements)
1
15
0
Order By: Relevance
“…In the first-episode psychotic patients (FEP), it was observed that those with cannabis-associated psychosis presented a greater degree of positive symptoms and dissociation and were significantly worse in terms of overall functioning [ 96 ]. According to clinical observation, the authors concluded that cannabis use not only can be a predictor of FEP manifestation but may also influence the disease duration and outcome [ 96 , 97 ]. In cannabis users, in comparison to the non-user group, a process of improvement and recovery after a psychotic episode was found to worsen over time [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the first-episode psychotic patients (FEP), it was observed that those with cannabis-associated psychosis presented a greater degree of positive symptoms and dissociation and were significantly worse in terms of overall functioning [ 96 ]. According to clinical observation, the authors concluded that cannabis use not only can be a predictor of FEP manifestation but may also influence the disease duration and outcome [ 96 , 97 ]. In cannabis users, in comparison to the non-user group, a process of improvement and recovery after a psychotic episode was found to worsen over time [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis use disorder afflicts about 22% of cannabis users, and 13% develop cannabis dependence ( 25 ). Cannabis use may increase the risk of psychosis and hinder its treatment ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as reported by previous studies, patients who start using substances earlier in life are at risk for developing serious secondary psychiatric disorders, such as psychoses. Two studies from 2021, by Ricci et al reported a link between prolonged cannabis use and development of first-episode psychosis associated with higher degrees of dissociative symptoms, observing higher DUP (Duration of Untreated Psychosis) in these patients as well [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%